A network pharmacology study of mechanism and efficacy of Jiawei Huanglian-Wendan decoction in polycystic ovary syndrome with insulin resistance. Issue 48 (2nd December 2022) - Shi, Na; Zhou, Yuhe; Ma, Hongbo
Abstract : Polycystic ovary syndrome (PCOS) is a common reproductive metabolic disorder, normally accompanied by insulin resistance (IR). The specific pathogenesis of this disease remains unclear. To identify the underlying pathogenesis of PCOS with IR and explore the potential efficacy and mechanism of Jiawei Huanglian-Wendan decoction (JHWD) by a network pharmacology approach. The effective components and the potential drug and disease-related targets are retrieved. Drug-disease overlapped targets are being obtained by Venny analysis. The construction of protein-protein interaction network relied on Search Tool for the Retrieval of Interacting Genes/Proteins database (STRING), after uploading drug-disease overlapped targets. The drug-component-target-disease interaction network map was displayed, after importing their data into Cytoscape 3.7.2 software. Bioinformatics analyses are being performed by Metascape and Kyoto Encyclopedia of Genes and Genomes databases, respectively. Further, molecular docking analysis was carried out using AutoDock software. Finally, the influence of JHWD is verified by means of traditional Chinese medicine syndrome score, the rate of resumption of normal menstrual cycles and regular ovulation, the blood lipid levels, the blood glucose and insulin levels, and the inflammatory cytokines in PCOS with IR patients. Four primary interaction networks of JHWD are constructed. The enrichment analysis of PCOS-IR-related targets demonstrated that the top enriched pathways in the development of PCOS with IR are pathways in cancer, metabolic, phosphoinositide-3-kinase-protein kinase B signaling, lipid and atherosclerosis, and mitogen-activated protein kinase signaling pathways. Molecular docking analysis revealed strong binding interactions of the key targets with the active components. Further confirmations showed that the active components of JHWD exhibited significant clinical efficacy in improving the clinical syndromes, menstrual cyclicity and ovulatory function, and significantly reducing the blood lipid levels, blood glucose and insulin levels, and inflammatory cytokines in PCOS with IR patients. The combination of the network pharmacological analysis and clinical validation stated that the active compounds in JHWD could regulate glycolipid metabolism, reduce IR, and exert anti-inflammatory effects in the treatment of PCOS with IR, promoting Chinese classical formulations.